The Innovator's Hypothesis - MICHAEL SCHRAGE (The MIT Press, 2014)
This is a modest book with an immodest argument: creative experimentation, with and within constraints, makes high-impact innovation a safer, smarter, simpler and more successful investment. It didnâ€™t start out that way; I had to experiment. Back in 1999, the Harvard Business School Press published Serious Play: How the Worldâ€™s Best Companies Simulate to Innovate, my book exploring how models, prototypes, and simulations shape innovation culture. The book proved unexpectedly influential. Companies all over the world invited me to work with them. I got unusually serious follow-ups from executive education classes and workshops at MIT. The opportunities were remarkable, the impact terrific. But I soon discovered something weird. Although they loved using models, prototypes, and simulations to â€œinnovate out loud,â€ most organizations seemed less interested in detailed â€œdeep dives.â€ Yes, technology companies wanted more collaborative prototyping, and professional service firms sought more dynamic visual simulations. But the majority wanted something different. They wanted their people innovating much faster, much better, and much cheaper. They wanted the organizationâ€™s best minds and brightest talents engaged in new ways. Enhancing human capital mattered as much as creating new products, services, or both. They desired effective change, not disruptive revolution. These companies craved a simple, fast, and frugal innovation capability. I confess: my immediate reaction was to repurpose my material and expertise. Iâ€™d better tailor and customize â€œrapid prototypingâ€ and â€œrapid simulationâ€ workshops to their briefs. But that frankly wasnâ€™t good enough. While modeling and prototyping were great for engineers, developers, and more technical folk, they lacked broader enterprise appeal. I listened more carefully to peopleâ€™s innovation ambitions, fears, and constraints. I realized I had to reinvent, not just repurpose. What could businesspeople collaboratively design to create or discover new innovation insights? Experiments. Business experiments. Get small teams from across the enterprise crafting business experiments that make their top managements sit up and lean forward. Push small teams to work collectively to come up with business hypotheses inspiring urgency and curiosity. But this wouldnâ€™t be â€œblue sky/anything goesâ€ experimentation. This would be experimentation within constraints: No blank checks, no unlimited budgets. No â€œinnovation vacationsâ€ for meditation and contemplation. Friendly rivalry between small teams. Clear deadlines. Explicit deliverables to top management. Opportunities to â€œexperiment out loudâ€ in ways commanding strategic attention and respect. These were fresh ingredients for cultural change and market impact. These improvised constraints evolved into the 5Ã—5 framework presented in this book. My initial clients and classes couldnâ€™t have been more open or receptive.